Permanent Internal Migration as Response to Food Shortage: Implication to Ecosystem Services in Southern Burkina Faso - Ouedraogo, ssa; Ouattara, Korodjouma; Kaboré/Sawadogo, Séraphine; Paré, Souleymane; Barron, Jennie (IntechOpen, 2012)
None